2014
DOI: 10.1086/675278
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Surgical Site Infection after Hepatic Resection

Abstract: A study of 7,388 consecutive patients after hepatic resection between 2011 and 2012 identified hepatolithiasis, cirrhosis, and intraoperative blood transfusion as the only independent risk factors of both incisional and organ/space surgical site infection (SSI). Patients with these conditions should be cared for with caution to lower SSI rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…However, in multivariate analysis, hepatolithiasis was an independent risk factor indicating postoperative SSIs in patients with PHCC. Similarly, Yang et al [25] have shown that hepatolithiasis was an independent risk factor of both incisional and organ/space SSI after liver resection in 1 study including 7388 patients with different liver diseases. Cholangiolithiasis often resulted in bile infection and liver abscesses due to biliary obstruction, while preoperative hepatobiliary infection may be closely associated with postoperative SSIs.…”
Section: Discussionmentioning
confidence: 87%
“…However, in multivariate analysis, hepatolithiasis was an independent risk factor indicating postoperative SSIs in patients with PHCC. Similarly, Yang et al [25] have shown that hepatolithiasis was an independent risk factor of both incisional and organ/space SSI after liver resection in 1 study including 7388 patients with different liver diseases. Cholangiolithiasis often resulted in bile infection and liver abscesses due to biliary obstruction, while preoperative hepatobiliary infection may be closely associated with postoperative SSIs.…”
Section: Discussionmentioning
confidence: 87%
“…Wound infection belongs in surgical site infection (SSI), which is the most common postoperative complication for hepatic resection 37 . Yang’s study 37 investigated the risk factors of SSI, and his results didn’t show a significant difference in incisional SSI when major resection (resection of 3 or more Couinaud liver segments) compared with minor resection (resection of fewer than 3 segments). However, MH and EH are both major resection, and our analysis result did show a higher wound rate in EH.…”
Section: Discussionmentioning
confidence: 99%
“…Patient demographic information and peri‐operative factors known to influence the risk of post‐operative infection were also collected. These included: age, race, smoking status, body mass index, malignancy, diabetes, American Society of Anesthesiologists (ASA) physical status, surgical chemoprophylaxis data (type, timing and dose), operative time, blood loss during surgery, an intra‐operative red blood cell transfusion and open versus minimally invasive surgery …”
Section: Methodsmentioning
confidence: 99%
“…These included: age, race, smoking status, body mass index, malignancy, diabetes, American Society of Anesthesiologists (ASA) physical status, surgical chemoprophylaxis data (type, timing and dose), operative time, blood loss during surgery, an intra-operative red blood cell transfusion and open versus minimally invasive surgery. 7,[20][21][22][23][24][25][26][27][28][29][30] Statistical analysis Bivariate analyses of the association between each variable and exposure to pre-operative hospitalization using the Student's t, Pearson v 2 , and Wilcoxon's rank-sum tests as appropriate were performed. We used univariable logistic regression to calculate unadjusted odds ratios (OR) and 95% confidence intervals (CI) for the association between pre-operative hospitalization and the risk of HAIs and SSIs in particular.…”
Section: Study Design and Patient Selectionmentioning
confidence: 99%